An improved bootstrap method introducing error ellipse for numerical analysis of fatigue life parameters. Issue 1 (15th October 2020) - Ge, Haiyan; Liu, Xintian; Fang, Yu; Wang, Haijie; Wang, Xu; Zhang, Minghui
Abstract : Purpose: The purpose of this paper is to introduce error ellipse into the bootstrap method to improve the reliability of small samples and the credibility of the S-N curve. Design/methodology/approach: Based on the bootstrap method and the reliability of the original samples, two error ellipse models are proposed. The error ellipse model reasonably predicts that the discrete law of expanded virtual samples obeys two-dimensional normal distribution. Findings: By comparing parameters obtained by the bootstrap method, improved bootstrap method (normal distribution) and error ellipse methods, it is found that the error ellipse method achieves the expansion of sampling range and shortens the confidence interval, which improves the accuracy of the estimation of parameters with small samples. Through case analysis, it is proved that the tangent error ellipse method is feasible, and the series of S-N curves is reasonable by the tangent error ellipse method. Originality/value: The error ellipse methods can lay a technical foundation for life prediction of products and have a progressive significance for the quality evaluation of products.